Comparative Studies of the Fibrinolytic System of Sera of Various Vertebrates - Niewiarowski, Stefan; Latallo, Zbigniew (Thrombosis and Haemostasis, 1959)
1. Comparative studies have been performed on the fibrinolytic system of sera of 18 vertebrates: man, monkey, dog, cat, ox, horse, ram, pig, rabbit, mouse, rat, hamster, guinea-pig, hen, duck, turkey, frog, fish.2. Spontaneously active plasmin in a considerable amount has been found only in guinea-pig euglobulin.3. The euglobulins from human, monkey, cat and dog sera can be activated by SK and by SKHP mixture.4. The euglobulin from hamster, rat, mouse, rabbit, bovine, horse, pig and ram sera can be activated by SKHP but not by SK.5. The euglobulins of lower vertebrates species cannot be activated by neither SK nor SKHP to any considerable value.6. The activation of fibrinolytic system runs parallel with the activation of proteolysis in human, bovine and guinea-pig euglobulin.7. The proactivator activity has been found in the species of human, monkey, dog and cat.8. Streptokinase activated human plasmin (SKHP) has been inhibited by most of the examined animals sera except of the human, monkey, dog and cat sera.9. It has been found that in the course of purification bovine plasminogen acquires the ability to be activated by SK. An inhibitor of activation occuring in bovine serum and euglobulin is probably removed by purification of plasminogen.10. The activation of plasmin in guinea-pig serum has been studied, it was found that spontaneous fibrinolytic activity generates slowly in guinea-pig euglobulin and reaches a maximum after 24 hours. Guinea-pig serum and shortly precipitated euglobulin could be activated by SKHP mixture only.11. Several possible explanations of the different behaviour of fibrinolytic systems in various animals have been discussed.